2023
DOI: 10.1021/acsmedchemlett.2c00491
|View full text |Cite
|
Sign up to set email alerts
|

Readily Accessible High-Throughput Experimentation: A General Protocol for the Preparation of ChemBeads and EnzyBeads

Abstract: Chemical-and enzyme-coated beads (ChemBeads and EnzyBeads) were introduced recently as a universal strategy for the accurate dispensing of various solids in submilligram quantities using automated instrumentation or manual dispensing. The coated beads are prepared using a resonant acoustic mixer (RAM)�an instrument that may be available only to wellestablished facilities. In this study, we evaluated alternative coating methods for preparing ChemBeads and EnzyBeads without the use of a RAM. We also evaluated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…To address these operational difficulties, we were excited by reports on the use of ChemBeads for the accurate measurement of reagents on small scale (10 μmol) and for dosing reagents that are poorly soluble in organic solvents. 11 Consequently, we decided to evaluate ChemBeads on the photoredox screening platform. Concurrently with our efforts, it was recently reported that there are no negative effects of adding beads to the reaction wells, including not impacting light penetration or disrupting efficient mixing.…”
Section: ■ Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To address these operational difficulties, we were excited by reports on the use of ChemBeads for the accurate measurement of reagents on small scale (10 μmol) and for dosing reagents that are poorly soluble in organic solvents. 11 Consequently, we decided to evaluate ChemBeads on the photoredox screening platform. Concurrently with our efforts, it was recently reported that there are no negative effects of adding beads to the reaction wells, including not impacting light penetration or disrupting efficient mixing.…”
Section: ■ Resultsmentioning
confidence: 99%
“…During the course of our screening plate development, we observed the poor solubility of the sodium carbonate base and Ni­(dtbbpy)­Cl 2 precatalyst in the organic solvents chosen and the hard-to-dose sticky nature of Si-1 complicated the screening process and raised potential reproducibility issues. To address these operational difficulties, we were excited by reports on the use of ChemBeads for the accurate measurement of reagents on small scale (10 μmol) and for dosing reagents that are poorly soluble in organic solvents . Consequently, we decided to evaluate ChemBeads on the photoredox screening platform.…”
Section: Resultsmentioning
confidence: 99%
“…37 ChemBeads can be prepared via resonant acoustic mixing, vortexing, or shaking by hand to coat solid reagents onto small chemically inert glass beads. 41 This process unifies the properties of the solids to those of the glass beads and increases requisite reagent mass, enabling faster and simpler dispensing, either manually or using automation. This technology was applied to the optimization of photoredox cross-couplings with the development of photocatalyst-and nickel catalyst-coated ChemBeads, resulting in expedited photoredox HTE reaction setup (Figure 4A).…”
Section: Experimentation For Photoredox Cross-couplingsmentioning
confidence: 99%
“…To expand HTE accessibility internally and streamline experiment setup, our group developed chemical-coated glass beads, or ChemBeads, as a technology that enables the reliable dispensing of solid reagents at the submilligram scale (Figure A) . ChemBeads can be prepared via resonant acoustic mixing, vortexing, or shaking by hand to coat solid reagents onto small chemically inert glass beads . This process unifies the properties of the solids to those of the glass beads and increases requisite reagent mass, enabling faster and simpler dispensing, either manually or using automation.…”
Section: Enabling High-throughput Experimentation For Photoredox Cros...mentioning
confidence: 99%
“…In parallel to identifying the scope of our LSC platform, we worked on rendering it amenable to high-throughput experimentation (HTE): We enabled 96-well screening at the micromolar scale using ChemBead technology. Using two example transformations, we juxtaposed the outcomes of a Pd-ligand screen to explore trends in stereoelectronic properties of Pd-catalysts using a standard Buchwald-ligand kit, with the ones for two commercially available copper species (Figure A). To our surprise, we did not observe any significant difference between the Pd species, where we would normally expect the effects of electron-releasing abilities and steric bulk to display a certain trend.…”
mentioning
confidence: 99%